Enhancing heterologous protection in pigs vaccinated with chimeric porcine reproductive and respiratory syndrome virus containing the full-length sequences of shuffled structural genes of multiple heterologous strains. Issue 18 (25th April 2017) - Tian, Debin; Cao, Dianjun; Lynn Heffron, C.; Yugo, Danielle M.; Rogers, Adam J.; Overend, Christopher; Matzinger, Shannon R.; Subramaniam, Sakthivel; Opriessnig, Tanja; LeRoith, Tanya; Meng, Xiang-Jin
Highlights: A chimera with full-length sequences of shuffled structural genes was generated. The chimera induced neutralizing antibodies in pigs against heterologous strains. The chimera conferred enhanced heterologous protection in pigs. The chimera VR2385-S3456 is a good PRRSV vaccine candidate. Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) is the causative agent of arguably the most economically important global swine disease. The extensive genetic variation of PRRSV strains is a major obstacle for heterologous protection of current vaccines. Previously, we constructed a panel of chimeric viruses containing only the ectodomain sequences of DNA-shuffled structural genes of different PRRSV strains in the backbone of a commercial vaccine, and found that one chimeric virus had an improved cross-protection efficacy. In this present study, to further enhance the cross-protective efficacy against heterologous strains, we constructed a novel chimeric virus VR2385-S3456 containing the full-length sequences of shuffled structural genes (ORFs 3-6) from 6 heterologous PRRSV strains in the backbone of PRRSV strain VR2385. We showed that the chimeric virus VR2385-S3456 induced a high level of neutralizing antibodies in pigs against two heterologous strains. A subsequent vaccination and challenge study in 48 pigs revealed that the chimeric virus VR2385-S3456 conferred an enhanced cross-protection when challenged with heterologous virus strain NADC20 or a contemporary heterologous strain RFLP 1-7-4. The results suggest that the chimera VR2385-S3456 may be a good PRRSV vaccine candidate for further development to confer heterologous protection.